Small Signal Parameter Extraction of III-V Heterojunction Surrounding Gate Tunnel Field Effect Transistor - ManjulaВ Vijh; R.S.В Gupta; SujataВ Pandey (Журнал нано- та електронної фізики)
This work presents simulation study and analysis of nanoscale III-V Heterojunction Gate All Around Tunnel Field Effect Transistor, along with the extraction of small signal parameters of the device. Transfer characteristics and output characteristics of the device were observed. The device is simulated for extraction of small signal parameters such as transconductance, gate-source capacitance, gate-drain capacitance, by varying doping concentration of drain region and channel length. Cut-off frequency of the device is also obtained. The results reported agree well with the data available in literature.